Bedroom body [videorecording (DVD)] : empowering a fit, confident you. - Miller, Angie (Angie Miller Fitness, 2012)
"Core focused total body conditioning program that uses combination exercises to train your heart and tone your muscles. Three targeted workouts are included: Buff Body Blast, Booty Burner, and Core & Polvic Floor."